Efficiency of Using Polymer Containers in Packaging Dairy and Meat Products - Gulmurod ugli, Pardayev Ruziboy; Doniyorovna, Fayzieva Shakhnoza (American Journal of Biology and Natural Sciences, 2026)
This article presents information on polymer packaging materials used to preserve milk and meat products in high quality for long-term storage.